Apresentações anatomopatológicas incomuns de doenças fúngicas - Silva, João Paulo Freitas da (2020)
Opportunistic fungal infections have been evidenced in recent decades mainly by the increase in their frequency. When considering superficial infections, such as dermatophytosis, they are of great importance and easy to recognize in the clinical routine of small and large animals. Although less frequent, deep fungal infections are of considerable importance, but are more difficult to diagnose. Collaboration between clinicians and pathologists is essential for the appropriate exam choice and subsequent therapeutic protocol establishment and institution. Seeking to help the suspicion and diagnosis of infrequent forms of systemic fungal infections, this dissertation aims to describe the anatomopathological lesions of three unusual fungal diseases. Invasive aspergilosis occurred in horses that had been sent to the stable early in its lives. These animals showed respiratory signs such as coughing and rattling, and at necropsy, multiple protruding pulmonary nodules on the lung surface were observed. The surface cut presented a greenish yellow appearance surrounded by a red halo. Disseminated penicilliosis occured in a dog and was caused by Penicillium pimiteouiense. In the clinical evaluation, a firm mass in the femur, with involvement of the adjacent musculature, and generalized superficial lymphadenomegaly were observed. Cases of penicilliosis involving this specie of the fungus had only been described in humans. Disseminated candidiasis was diagnosed in a dog. Because Candida sp. is a commensal agent, cutaneous or enteric form are more commonly observed while the dissemination to other organs occur less frenquently. In the case presented here, it was possible to visualize several ulcerated areas in the skin, oral mucosa and intestines, in addition to whitish nodules in the liver.